Intra-household resource allocation : an overview - Haddad, Lawrence James; Hoddinott, John; Alderman, Harold; The World Bank (Washington : The World Bank, 1994)
This book surveys a diverse body of evidence on intrahousehold resources allocation issues. Emphasis is placed on why and how a better understanding of intrahousehold processes will strengthen policy formulation and implementation, and how that better understanding may be achieved.
Includes bibliography pp. 73-85
usc 20/02/2019
Loans
Keywords: Households; Economic development; Resource allocation; Income distribution